Pressure ulcer prevention among nurses in Malaysia: a cross-sectional survey - Seman, Nordianna; Maripen Kuta, Nasreen; Mamat, Nur Liyana Nabihah (Universitas Airlangga, 2025)
Introduction: Pressure ulcers (PUs) remain a global health issue, contributing to increased morbidity and premature mortality. Nurses play a central role in prevention, underscoring the significant role in addressing this issue through the rapidly evolving healthcare environment. Clinical competence requires sound knowledge, attitude, and practice that contribute to excellent outcomes, focusing on individual patient needs and the changing conditions of the healthcare setting. Therefore, this study is aimed to evaluate nurses’ knowledge, attitudes, and practices on preventing PUs. Methods: This quantitative cross-sectional survey was conducted across three public hospitals in Malaysia. Using the two-stage cluster sampling strategy, registered nurses were recruited (n=210). Data were collected using a self-administered questionnaire with good reliability scores (α=0.76–0.82). Descriptive and inferential analyses were computed to address the objectives. Results: Findings revealed low knowledge score (M=67.07, SD=7.78), neutral attitudes (M=73.28, SD=10.37), and excellent practices for pressure ulcer prevention (M=86.78, SD=15.05). Nurses’ attitudes were positively correlated with their practices (p<0.05), though no significant associations were observed between demographic factors and knowledge, attitude, and practice (p>0.05). Conclusions: The findings provide valuable information about nurses' understanding of pressure ulcer prevention that may assist with future strategies and interventions to enhance the knowledge and attitudes among practicing nurses. The identified gaps may be filled with targeted interventions, and future studies looking at variables affecting nurses' attitudes and practices, and the effectiveness of educational interventions can be beneficial.